Preparation and properties of novel epoxy composites containing electrospun PA6/F‐MWNTs fibers. Issue 11 (4th June 2016) - Liao, Guiying; You, Qingliang; Xia, Hua; Wang, Dongsheng
Abstract : The Nylon 6 (PA6)/the functionalized multiwalled carbon nanotubes (F‐MWNTs) fibrous membranes were fabricated by electrospinning, and then incorporated into an epoxy matrix. Their morphology, thermal stability, mechanical properties, thermal conductivities, and electrical resistivity were investigated. The electrospun PA6/F‐MWNTs fibers performed as a skeleton in the epoxy matrix, and the well interfacial adhesion between the epoxy matrix and the PA6/F‐MWNTs fibers leads to high mechanical properties of composites. The PA6 serves as an intermediate layer and alleviates the modulus mismatch between the stiff MWNTs and the soft epoxy matrix. The thermal conductivities of the epoxy composites increase by 27.3, 35.0, and 36.1%, respectively, with 0.5, 1 and 1.5 wt% F‐MWNTs loading in the PA6/F‐MWNTs fibers. At the same time, the PA6 simultaneously retains the high electrical resistivity of these epoxy composites. POLYM. ENG. SCI., 56:1259–1266, 2016. © 2016 Society of Plastics Engineers